Diagnostic Accuracy of Lung Ultrasound Performed by Novice Versus Advanced Sonographers for Pneumonia in Children: A Systematic Review and Meta‐analysis. (16th July 2019) - Tsou, Po‐Yang; Chen, Kenneth P.; Wang, Yu‐Hsun; Fishe, Jennifer; Gillon, Jason; Lee, Chien‐Chang; Deanehan, Julia K.; Kuo, Pei‐Lun; Yu, Daniel Ta Yo
Abstract: Background: Childhood pneumonia is a leading cause of mortality worldwide. Growing evidence suggests that lung ultrasound (LUS) may be a reliable diagnostic alternative to chest x‐ray for childhood pneumonia. However, it is unclear whether sonographer experience affects the diagnostic accuracy of LUS. We summarize the diagnostic accuracy of LUS for pneumonia and compare the performance between novice and advanced sonographers with a systematic review and meta‐analysis. Methods: We searched PubMed and EMBASE from inception to February 2018 for eligible studies that evaluated the utility of LUS in children suspected of having pneumonia against the reference standard of either imaging results alone or a combination of clinical, laboratory, and imaging results. We reported the study using the Preferred Reporting Items for a Systematic Review and Meta‐analysis of Diagnostic Test Accuracy Studies. We used QUADAS‐2 to appraise the included studies' methodologic quality. We employed a random‐effect bivariate model and a hierarchical summary receiver operating characteristic curve to evaluate LUS's performance characteristics. We conducted subgroup analyses and meta‐regression based on level of sonographer training to summarize and compare LUS's diagnostic accuracy for pneumonia between novice (training ≤ 7 days) and advanced sonographers. Results: Twenty‐five studies ( n  = 3, 353) were included in the meta‐analysis. For diagnosing pneumonia, LUS demonstrated an overall sensitivity of 0.94 (95% confidence interval [CI] = 0.89 to 0.97), specificity of 0.92 (95% CI = 0.78 to 0.98), positive likelihood ratio of 12.40 (95% CI = 4.00 to 38.10), and negative likelihood ratio of 0.07 (95% CI = 0.04 to 0.12), with an area under ROC curve of 0.97 (95% CI = 0.95 to 0.98). Meta‐regression revealed a significant difference in the diagnostic accuracy for pneumonia for LUS between novice and advanced sonographers (p < 0.01). Conclusion: LUS can accurately diagnose pneumonia in children. However, this test demonstrates operator‐dependent variability, with more experienced sonographers having higher diagnostic accuracy. Further work on evidence‐based educational methods to train novice sonographers in LUS is required.